Bone marrow derived stromal cells from myelodysplastic syndromes are altered but not clonally mutated in vivo - Jann, Johann-Christoph; Mossner, Maximilian; Riabov, Vladimir; Altrock, Eva; Schmitt, Nanni; Flach, Johanna; Xu, Qingyu; Nowak, Verena; Obländer, Julia; Palme, Iris; Weimer, Nadine; Streuer, Alexander; et al. (Nature Communications, 2021)
The bone marrow (BM) stroma in myeloid neoplasms is altered and it is hypothesized that this cell compartment may also harbor clonal somatically acquired mutations. By exome sequencing of in vitro expanded mesenchymal stromal cells (MSCs) from n = 98 patients with myelodysplastic syndrome (MDS) and n = 28 healthy controls we show that these cells accumulate recurrent mutations in genes such as ZFX (n = 8/98), RANK (n = 5/98), and others. MDS derived MSCs display higher mutational burdens, increased replicative stress, senescence, inflammatory gene expression, and distinct mutational signatures as compared to healthy MSCs. However, validation experiments in serial culture passages, chronological BM aspirations and backtracking of high confidence mutations by re-sequencing primary sorted MDS MSCs indicate that the discovered mutations are secondary to in vitro expansion but not present in primary BM. Thus, we here report that there is no evidence for clonal mutations in the BM stroma of MDS patients.